Sudden Cardiac Death As a Mystery of The Sports World - Current Insight Into Risk Factors, Diagnosis and Management of The Most Common Underlying Causes - Kędzia, Jakub; Duda, Joanna; Racisz, Kinga; Racisz, Paweł; Obcowska, Alicja; Walendzik, Aleksandra (Quality in Sport, 2025)
Introduction and aim of the study: With the growing popularity of physical activity, sudden cardiac death has become a significant concern among both professional and recreational athletes. This study aims to review current knowledge on risk factors, diagnosis, and management of the most common causes of sudden cardiac arrest and sudden cardiac death in athletes, offering practical insights for healthcare professionals. Materials and methods: This review is based on literature sourced from databases such as PubMed and Google Scholar. Keywords used included: “sudden cardiac death,” “sudden cardiac arrest,” “sudden cardiac death in sport,” and “sudden cardiac death in athletes.” Results: Several risk factors for sudden cardiac death were identified, including age, sex, ethnicity, type and intensity of sport, and abnormalities on ECG screening. The causes of sudden cardiac death vary by age; in athletes under 35, the most frequent conditions include hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, long QT syndrome, and Brugada syndrome. These conditions were analyzed with respect to diagnosis, management, and potential complications. Conclusion: Sudden cardiac arrest and sudden cardiac death are critical concerns in the athletic population. All discussed conditions are genetically determined, so a family history of unexplained sudden death or cardiogenic syncope should raise clinical suspicion. Early detection, proper risk assessment, and timely intervention can significantly reduce the risk of fatal outcomes. Increasing physician awareness of these conditions is essential to improve recognition and prevention among at-risk athletes.